ANTIBACTERIAL ACTIVITY OF PARIJOTO FRUIT EXTRACT (Medinilla speciosa) ON BACTERIA EXTENDED SPECTRUM BETALACTAMASE (ESBL) ESCHERICHIA COLI AND METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) - Rizka Ayu Wahyuni; Inesya Yuliana Putri; Eden Lambang Jayadi; Muhammad Evy Prastiyanto (Poltekkes Kemenkes Pakassar, 2019)
Infection is one of the causes of death and pain that occurs mainly in Indonesia. Infections can be caused by Gram-negative and gram-positive bacteria such as the Extended Spectrum Beta Laktamase, Escherichia coli (E. coli) and Methicilin Resistant Staphylococcus aureus (MRSA), which are one of the Strain of S. aureus. The study aims to determine the antibacterial activity of Aquadest extracts, Methanol, Ethyl acetat and N-hexane of Parijoto (M. speciosa), MIC and MBC values against ESBL E. coli and MRSA bacteria. The samples in this study were Parijoto fruit extracts concentration 100 mg/mL. In this research antibacterial activity using the method of diffuse with the MHA media, while to know the value of MIC using methods dilution with MHB and MBC media using BAP media. The results were characterized by the formation of the largest barrier zone on the 11.6 mm methanol extract, the smallest MIC yield on N-hexane and aquadest extracts with a value of 50 mg/mL, whereas on MBC tests each extract resulted in a value of 50 mg/mL and While the hate zone against the MRSA bacteria is obtained the largest diameter of the hate zone in the N-hexane solvent, which is 23.17 mm in average, the largest MIC value in the aquadest solvent at a concentration of 50 mg/ml, and the largest MBC value in methanol solvent Concentrations of 50 mg/ml. So that it can be concluded Parijoto fruit extract has the potential as an alternative substitute for chemical antibiotics against MRSA bacteria whereas for bacteria ESBL E. coli has no potential as an alternative to antibiotic substitute.Keywords : Antibacterial, Escherichia coli, Methicilin Resistant Staphylococcus aureus, Medinilla speciosa